Einfluss des Windschubes auf die Atlantische Umwälzbewegung - Tuchen, Franz Philip (2013)
The Atlantic Meridional Overturning Circulation (AMOC) influences North Atlantic climate and is responsible for relatively warm temperatures in northern Europe compared to other places at same latitudes (Cunningham et al., 2007). Therefore the exact mechanisms and reactions to external impacts and fluctuations of different parameters are very important parts of current research for the reason that a certain wind stress field could possibly give information about the future strength of the AMOC. Within the scope of this Bachelor thesis ten model runs of the Kiel Climate Model (KCM) are driven with global wind forcing by ERA40 and NCEP wind stress datasets to observe the influence of wind stress on AMOC. It shows that the Overturning Circulation has a decreasing trend during the observed period from 1958-2001, while at the same time wind stress is increasing. This opposing trend allows the assumption that other processes like heat fluxes or density driven transports superpose the influence of the wind stress and that the decadal trend of the AMOC is hardly influenced by windstress (Cunningham et al., 2007). Furthermore a negative correlation between AMOC and wind stress, meaning that an increase of AMOC would lead to a decrease in wind stress, can be excluded (Eden et al., 2001). It rather shows, that wind stress is at least partly responsible for interannual variabilities. This influence has its maximum impact with a time delay ("lag") of three years after an event in wind stress. The highest positive correlations are found in the North Atlantic region in a belt from the US east coast to the British Islands. Here an increase of the windstress curl would lead to maximum changes of AMOC transport strength with a time delay of three years. In this thesis wind driven water mass transport is described by the Ekman transport, which makes up about 10% of the total Overturning transport. The variability of Ekman transport and zonal wind fluctuations are quite strong in the northern Atlantic and can significantly ...